2022
DOI: 10.1186/s12916-022-02599-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of metformin therapy in patients with cancer: a meta-analysis of 22 randomised controlled trials

Abstract: Background To investigate whether metformin monotherapy or adjunctive therapy improves the prognosis in patients with any type of cancer compared to non-metformin users (age ≥18). Methods Databases (Medline, Embase, and the Cochrane Central Register of Controlled Trials) and clinical trial registries (ClinicalTrials.gov; the World Health Organization International Clinical Trials Registry Platform) were screened for randomized, controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 87 publications
0
13
0
1
Order By: Relevance
“…Despite glucose-lowering drugs reducing blood sugar, they provide limited cardiovascular benefits, and often cause weight gain, especially with insulin and sulfonylurea drugs [ 16 , 17 ]. While metformin is a well-known glucose-lowering drug with benefits, it is not recommended for all patients, such as those with certain cancers, and has shown mixed results in terms of progression-free survival, with better outcomes in patients with reproductive cancers and worse outcomes in those with digestive system cancers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite glucose-lowering drugs reducing blood sugar, they provide limited cardiovascular benefits, and often cause weight gain, especially with insulin and sulfonylurea drugs [ 16 , 17 ]. While metformin is a well-known glucose-lowering drug with benefits, it is not recommended for all patients, such as those with certain cancers, and has shown mixed results in terms of progression-free survival, with better outcomes in patients with reproductive cancers and worse outcomes in those with digestive system cancers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian Journal of Health Review, Curitiba, v. 7, n. 1, p. 2600-2611, jan./fev., 2024 terapia com metformina é potencialmente benéfica para cânceres do sistema reprodutivo, incluindo mama, ovário, endométrio e próstata (WEN, et al, 2022).…”
Section: Resultsunclassified
“…Results from clinical studies regarding the anti-cancer effects of metformin are rather controversial. Indeed, while some retrospective-case control studies, have shown that metformin is able to reduce overall cancer incidence and mortality by 10%–40% ( IDF, 2021 ), RCTs failed to show a significant reduction in cancer incidence and mortality ( Stevens et al, 2012 ; Wen et al, 2022 ). This discrepancy could be due, at least in part, to the short follow-up time and/or to the biological heterogeneity of cancer.…”
Section: Anti-diabetic Drugs Repositionable As Potential Anti-cancer ...mentioning
confidence: 99%